ANALISIS KREDIT BERMASALAH DILIHAT DARI STANDAR NON PERFORMING LOAN (NPL) PADA PT. BANK MANDIRI (PERSERO) TBK - Kurniati, Titi; Nurhayati, Nurhayati (prodima@fe.uika-bogor.ac.id, 2020)
This study aims to examine how much Non Performing Loans at PT. Bank Mandiri (Persero) Tbk registered on the Stock Exchange for the 2014-2018 period. This research method uses descriptive methods including NPL analysis and hypothesis testing using significance test (t test). The results of the study stated that